Outcome of Spine Fixation for Unstable Fractures at Dorslumbar Junction Including Fractured Vertebrae in Pedicular Screw Fixation - Waleed Ali, Anwar Shah, Arshan Munir, Mohammad Mushtaq, Maaz Ullah, Fazli Wahab, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: In the present study, the researchers want to establish the outcome of spine fixation for unstable fractures at the dorsolumbar junction, including fractured vertebrae, while using pedicular screw fixation techniques. Study Design: Prospective study Place and Duration: The study was conducted at Orthopaedics Department, Hayatabad Medical Complex, Peshawar and Neurosurgery Department, Frontier Medical and Dental College, Abbottabad for the duration of six months from May 2021 to October 2021. Methods: There were hundred and nineteen patients of both genders had unstable fracture at dorslumbar junction. Patients were aged between 20-55 years. Transpedicular screws were used to secure the fractured vertebra. Both radiographic and clinical assessments of back pain and impairment were conducted using the Visual Analogue Scale (VAS) and the Oswestry Disability Index (ODI) to evaluate patients (ODI). Before surgery, shortly after surgery, and eight months afterwards, all of these data were assessed. SPSS 23.0 version was used to analyze complete data. Results: Mean age of the patients was 33.5±5.42 years. 85 (71.4%) cases were males and 34 (28.6%) patients were females. Falling from the height was the most common reason found in 60 (50.4%) cases followed by road traffic accident 45 (37.8%) cases and 14 (11.8%) were others. L1 fractures were majority found in 67 (56.3%) cases followed by L2 in 40 (33.6%) cases. Post-operatively, we found significantly improvement in Cobb angle, anterior vertebral height, posterior vertebral height and sagittal index with p value <0.05. Oswestry disability index (ODI) was improved to 41.13±19.42% from 70.6±16.43%. Mean pain score (VAS) was reduced to 1.01±5.23. Post-operatively only 7 (5.9%) patients had complications. Conclusion: Our patients who had transpedicular screw fixation, which included fixing the broken vertebrae, had outstanding radiological and clinical outcomes. Treatment of the fractured vertebra in transpedicular screw fixation of dorsolumbar spine fractures is, thus, highly recommended.